Voltage-Gated Sodium Channel Modulation by a New Spider Toxin Ssp1a Isolated From an Australian Theraphosid - Dongol, Yashad; Choi, Phil M.; Wilson, David T.; Daly, Norelle L.; Cardoso, Fernanda C.; Lewis, Richard J. (Frontiers in Pharmacology, 2021)
Given the important role of voltage-gated sodium (NaV) channel-modulating spider toxins in elucidating the function, pharmacology, and mechanism of action of therapeutically relevant NaV channels, we screened the venom from Australian theraphosid species against the human pain target hNaV1.7. Using assay-guided fractionation, we isolated a 33-residue inhibitor cystine knot (ICK) peptide (Ssp1a) belonging to the NaSpTx1 family. Recombinant Ssp1a (rSsp1a) inhibited neuronal hNaV subtypes with a rank order of potency hNaV1.7 > 1.6 > 1.2 > 1.3 > 1.1. rSsp1a inhibited hNaV1.7, hNaV1.2 and hNaV1.3 without significantly altering the voltage-dependence of activation, inactivation, or delay in recovery from inactivation. However, rSsp1a demonstrated voltage-dependent inhibition at hNaV1.7 and rSsp1a-bound hNaV1.7 opened at extreme depolarizations, suggesting rSsp1a likely interacted with voltage-sensing domain II (VSD II) of hNaV1.7 to trap the channel in its resting state. Nuclear magnetic resonance spectroscopy revealed key structural features of Ssp1a, including an amphipathic surface with hydrophobic and charged patches shown by docking studies to comprise the interacting surface. This study provides the basis for future structure-function studies to guide the development of subtype selective inhibitors.